(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2018)
The physicochemical and microbiological characteristics of wastewater samples from Old Sokoto Abattoir in Sokoto North Local Government Area, Sokoto state, Nigeria were studied over four weeks period. The physicochemical parameters of the wastewater samples studied namely pH, temperature, biochemical oxygen demand (BOD), dissolved oxygen (DfO), phosphate, nitrate, and chemical oxygen demand (COD) were within the standard limit for wastewater to be discharged into the environment. Heavy metals like nickel, copper, and lead were not detected (ND) except for iron with a concentration range from 0-0.64 mg/L. Wastewater samples for week 1 had a higher bacterial count of 270x105 CFU/mL than wastewater samples for the other weeks. The total viable count for all the samples exceeded the limit of 1x102 CFU/mL, which was between 4.1x105 – 27.0x105. All the wastewater samples were found to harbour coliform organisms in numbers greater than the required WHO standard (1x102 CFU/mL) for water. The MPN count of wastewater was ranged from 190-1100 MPN/100 mL. The bacterial species isolated were E. coli (33.3%), E. aerogenes (20%), S. aureus (6.66%), K. pneumoniae (6.66%), Proteus vulgaris (13.3%), Citrobater freundii (6.66%), Bacillus licheniformis (6.66%), and Bacillus spp. The fungal isolates were Mucor spp (12.5%), Aspergillus niger (37.5%), Aspergillus terreus (12.5%), Sporothrix schenkii (12.5%), Rhodotorula spp. (12.5%), and Penicillium spp. (12.5%). This study showed that the isolation and population of microorganisms from wastewater in Old Sokoto Abattoir is an indication that the wastewater was highly polluted with microbial load and can cause an environmental hazard if not treated.